Effect of botanical powders and the assassin bug, Alloeocranum biannulipes Mont. and Sign. (Hemiptera: Reduviidae) against Dinoderus porcellus Lesne (Coleoptera: Bostrichidae) infesting yam chips [version 2; peer review: 2 approved, 1 approved with reservations] - Kitherian SAHAYARAJ; Antonio SINZOGAN; Manuele TAMO; Joelle TOFFA; Yêyinou Laura Estelle LOKO; Armand VODOUNNON; Innocent DJEGBE (Open Research Africa, 2025)
Background Dinoderus porcellus Lesne (Coleoptera: Bostrichidae) is the main pest of stored dried yam chips that causes significant losses in less than 3 months. The assassin bug, Alloeocranum biannulipes (Montrouzier & Signoret) (Hemiptera: Reduviidae) and the African mahogany (Khaya senegalensis (Desv.) A. Juss. (Meliaceae)), the ackee (Blighia sapida K. Koenig (Sapindaceae)), and bridelia (Bridelia ferruginea Benth. (Euphorbiaceae)) leaf powders have proven to be efficient in the control of this pest. Methods This study aims to evaluate the compatibility of the leaf powders of these medicinal plants and the predator A. biannulipes in the integrated management of D. porcellus under laboratory and farm conditions. Various leaf powders were tested at a concentration of 6% (w/w) with or without the predator. Infested yam chips without any treatment served as negative control and those mixed with a synthetic insecticide as positive control. The mortality rate of D. porcellus was recorded under laboratory conditions. While, the dynamic population of D. porcellus, their damage, and weight loss of yam chips were recorded 8 weeks after treatment under farm conditions. Results The results revealed that no combination of leaf powders and predators could induce complete mortality of D. porcellus like the synthetic insecticide. No significant difference in terms of the survival of A. biannulipes exposed to botanical powders was observed compared to the positive control. Under farm conditions, B. ferruginea leaf powder showed a sub-lethal effect on the predator A. biannulipes and no impact on the abundance of D. porcellus. However, the survival of D. porcellus was significantly reduced by the combination of K. senegalensis leaf powder and A. biannulipes, which did not allow the reproduction of the predator. Conclusions Our results suggest that an augmentative biological control program with the release of A. biannulipes after the introduction of K. senegalensis leaf powder is practicable for the management of D. porcellus in yam chips.